Art and culture in the pandemic: Convergences and innovations of cultural artistic spaces with virtual spaces (Revista Internacional de Folkcomunicação, 2021)
This paper aims at discussing how some cultural spaces, such as Sesc São Paulo, implemented changes to continue offering artistic and cultural activities during the pandemic period. Starting from researching current scientific articles and periodical publications that dealt with the subject in the last two years and allowed access to a series of information already systematized, this paper will discuss how the production, distribution and consumption of artistic and cultural goods were restructured and reformatted following the migration to an online format.